Ligand and structure-based models for the prediction of ligand-receptor affinities and virtual screenings Development and application to the beta(2)-adrenergic receptor - Vilar, Santiago (Journal of computational chemistry, 2010)
(c) 2009 Wiley Periodicals, Inc.